FUHAR: A transformable wheel-legged hybrid mobile robot - Mertyuz, Irem; Tanyildizi, Alper K.; Tasar, Beyda; Tatar, Ahmet B.; Yakut, Oguz (Elsevier, 2020)
This paper introduces a mobile robot with a new type of transformable wheel legs that can be used for flat and rough terrain. It integrates the stability and maneuverability of a wheeled robot and the legged robot's obstacle climbing capacity using a transformable mechanism with wheel legs. With a transformation structure based on a four-bar mechanism, these two modes can be easily changed. This paper analyzes the movements for the proposed robot in wheeled and legged mode. Dynamic modeling and design of a control system were obtained. Then, the obstacle climbing strategies under legged modes were carried out. Finally, on the basis of the simulation, a prototype of the proposed robot was designed and produced. The results from the experiments validate the efficiency of the designed hybrid mobile robot. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Mobile robot; Transformable wheel-legged robot; Motion analysis; Obstacle avoidance; Dynamic model